Titanium and zirconium co-doped carbon-coated lithium iron phosphate material and its preparation method and application

The carbon-coated lithium iron phosphate material co-doped with titanium and zirconium addresses the limitations of LiFePO4 by enhancing conductivity and compacted density, resulting in high energy and power density performance for lithium-ion batteries.

JP7600510B2Active Publication Date: 2024-12-17HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023529058
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2022-11-11
Publication Date
2024-12-17
Estimated Expiration
2042-11-11

Smart Images

  • Figure 0007600510000001
    Figure 0007600510000001
  • Figure 0007600510000002
    Figure 0007600510000002
  • Figure 0007600510000003
    Figure 0007600510000003
Patent Text Reader

Abstract

The present invention relates to a titanium and zirconium co-doped carbon-coated lithium iron phosphate material and its preparation and application. The material has the chemical formula Li 1-y Zr y Fe 1-x Ti x PO4 / C (where 0.001≦x≦0.05, 0.001≦y≦0.02), titanium is doped at the Fe site, and zirconium is doped at the Li site. In the manufacturing method, the mixture of iron phosphate, lithium carbonate, carbon source, titanium source, and zirconium source mixed in a liquid phase solvent is ground into a slurry with a predetermined particle size by a ball mill and a sand mill, then granulated by a spray drying means, and finally the dried spray material is sintered in an atmospheric furnace. This material is applied as a cathode material in lithium ion batteries. In the present invention, the ion and electron transport ability of lithium iron phosphate is effectively enhanced by doping titanium and zirconium elements into the carbon-coated lithium iron phosphate, and the compressed density of the material is improved, making the material very suitable as a cathode material for high energy and high power density lithium ion power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Cross reference] This application claims priority to a Chinese patent application filed with the China Patent Office on December 29, 2021, with application number 202111629862.7 and title "Titanium and zirconium co-doped carbon-coated lithium iron phosphate material and its manufacturing method and application," the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to the technical field of new energy materials and their manufacture, and in particular to a titanium and zirconium co-doped carbon-coated lithium iron phosphate material, which can be applied to lithium ion power batteries as a high performance cathode material, and a method for manufacturing the same. [Background technology]

[0003] In 1997, J. Goodenough et al. reported that lithium iron phosphate (LiFePO4) could be used as a cathode material for lithium-ion batteries. This research caused a great sensation in the academic community, and at the same time, the industrialization of LiFePO4 began. LiFePO4 has the advantages of long cycle life, high safety, and low cost, so it has rapidly become an important cathode material for lithium-ion batteries. Lithium-ion batteries using this material as a cathode material have been widely applied in fields including portable electronic devices, automobiles, ships, and energy storage. In recent years, with the rapid development of China's new energy automobile industry, the demand for lithium-ion power batteries is increasing, and the proportion of power batteries installed using LiFePO4 as a cathode material is gradually increasing, so the market for LiFePO4 cathode material is developing rapidly.

[0004] However, compared with other cathode materials, especially ternary cathode materials, LiFePO4 still has low specific capacity and compacted density, and its ionic and electronic conductivity is low, resulting in poor charge and discharge capability under high current. Such defects significantly limit the improvement of energy density and power density of LiFePO4. To improve the electrochemical properties and compacted density of LiFePO4, researchers often use technological means such as shape and size control, carbon coating, and ion doping to overcome the inherent defects of this material. Metal ion doping is an important method to improve the electrochemical properties of LiFePO4. For example, when titanium ions are doped into the Fe site of this material, its lithium ion and electron transport capability is effectively enhanced [J.Power Sources,189(2009)440;J.Electrochem.Soc.,160(2013)A3148;CN108598383A;CN111498825A]. However, the effect of titanium ion doping on the compression density of LiFePO4 material is not sufficient. In recent years, related research has shown that zirconium ions can be doped into the Li site of LiFePO4 material, which can not only adjust the particle size and shape of LiFePO4 material, but also optimize the carbon coating effect to make the interaction between carbon material and LiFePO4 closer [J.Alloys Compd.,739(2018)529;J.Electrochem.Soc.,166(2019)A410;CN108682833B]. Therefore, zirconium ion doping can improve the compression density of LiFePO4 material.

[0005] Thus, by synergistically doping titanium ions and zirconium ions into LiFePO4 material, the inherent defects of this material can be overcome, its intrinsic electrical conductivity and compaction density can be effectively improved, and its energy density and power density can be significantly improved.

[0006] Therefore, developing titanium and zirconium co-doped carbon-coated lithium iron phosphate materials is a technical problem to be solved. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in view of the above-mentioned defects and needs for improvement in the prior art, and proposes a titanium and zirconium co-doped carbon-coated lithium iron phosphate material with high energy density and high power density obtained by doping the Fe site and Li site of LiFePO4 material with metallic titanium ions and zirconium ions, respectively, and its manufacturing method and application. The synergistic doping of titanium ions and zirconium ions can effectively improve the electrochemical properties and compaction density of LiFePO4 material. [Means for solving the problem]

[0008] The present invention is realized by the following technical aspects:

[0009] The titanium and zirconium co-doped carbon-coated lithium iron phosphate material has the chemical formula Li 1-y Zr y Fe 1-x Ti x PO4 / C (where 0.001≦x≦0.05, 0.001≦y≦0.02), titanium is doped on the Fe site, zirconium is doped on the Li site, and the carbon content is 0.5-5.0 wt%.

[0010] In the method for producing the titanium and zirconium co-doped lithium iron phosphate material coated with carbon, a mixture of iron phosphate, lithium carbonate, a carbon source, a titanium source, and a zirconium source mixed in a liquid phase solvent is ground into a slurry having a predetermined particle size using a ball mill and a sand mill, and then granulated by a spray drying means. Finally, the dried sprayed material is sintered and pulverized in an atmospheric furnace to obtain the titanium and zirconium co-doped lithium iron phosphate material coated with carbon.

[0011] The method for preparing the titanium and zirconium co-doped carbon-coated lithium iron phosphate material includes: (1) weighing iron phosphate, lithium carbonate, a titanium source, and a zirconium source in an elemental molar ratio of Li:Zr:Fe:Ti:P=1-y:y:1-x:x:1 (where 0.001≦x≦0.05, 0.001≦y≦0.02) and mixing them in a liquid phase solvent; (2) adding a carbon source to the mixture obtained in the step (1), and then polishing the mixture with a ball mill and a sand mill so that the particle size of the slurry is controlled to 0.1 to 0.8 μm; (3) spray-drying the slurry obtained in the step (2) under conditions of an atomization frequency of 20 to 80 Hz, an air inlet temperature of the heated air of 100 to 300°C, and an air outlet temperature of 50 to 200°C; (4) The dried sprayed material obtained in the step (3) is pre-sintered in an atmosphere furnace in which a protective gas is passed at 300 to 500°C for 2 to 5 hours, and then sintered at 500 to 900°C for 5 to 15 hours to produce a titanium and zirconium co-doped carbon-coated lithium iron phosphate material.

[0012] In the method for producing the titanium and zirconium co-doped carbon-coated lithium iron phosphate material, the titanium source is one or more of titanium dioxide, titanyl sulfate, and tetrabutyl titanate with titanium tetrachloride. The zirconium source is one or more of zirconium oxide, zirconium hydroxide, zirconium nitrate, and zirconium phosphate. The liquid phase solvent is either one or both of deionized water and absolute ethanol. The carbon source is one or more of glucose, sucrose, citric acid, and polyethylene glycol, and the amount of the carbon source added is an amount that allows the carbon content in the final product to be 0.5 to 5.0 wt%. The atomization frequency is 60 Hz, the air inlet temperature is 200°C, and the air outlet temperature is 100°C, the preliminary sintering is performed at a temperature of 400°C for 3 hours, and the sintering is performed at a temperature of 800°C for 10 hours.

[0013] The carbon-coated lithium iron phosphate material co-doped with titanium and zirconium according to claim 1 and the carbon-coated lithium iron phosphate material co-doped with titanium and zirconium produced by the production method according to any one of claims 1 to 9 are used as positive electrode materials in lithium ion batteries. Effect of the Invention

[0014] In the titanium and zirconium co-doped carbon-coated lithium iron phosphate material and the manufacturing method thereof according to the present invention, the raw materials used are inexpensive and abundant, the process is simple, and industrial batch production is possible. By simultaneously adding a titanium source and a zirconium source to the reaction system, doping of the Fe site of the LiFePO4 material with titanium ions and doping of the Li site with zirconium ions can be realized. The doping of titanium ions can improve the intrinsic conductivity of the LiFePO4 material, and the doping of zirconium ions can increase the compaction density by adjusting the shape and size and optimizing the carbon coating effect.

[0015] The co-doping of titanium ions and zirconium ions can produce a synergistic effect, which enhances the lithium ion and electron transport ability of the LiFePO4 material while effectively improving the packing density of the material. The resulting titanium and zirconium co-doped carbon-coated lithium iron phosphate material has a discharge capacity of 158.0 mAhg at 0.1 C. -1 The initial coulombic efficiency exceeded 96.0%, and the discharge capacity at 1C was 145.0mAhg -1 and the compressed density is over 2.50gmL -1 It is highly suitable as a cathode material for high-energy and high-power density lithium-ion power batteries. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows the XRD spectra of carbon-coated lithium iron phosphate and carbon-coated lithium iron phosphate co-doped with zirconium and titanium. [Diagram 2] FIG. 2 is an SEM image of the zirconium and titanium co-doped carbon coated lithium iron phosphate of the present invention. [Diagram 3] FIG. 3 shows the first charge / discharge diagrams of carbon-coated lithium iron phosphate and carbon-coated lithium iron phosphate co-doped with zirconium and titanium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The titanium and zirconium co-doped carbon-coated lithium iron phosphate material of the present invention is prepared by a specific process by doping metallic titanium ions and zirconium ions into the Fe site and Li site of LiFePO4 material, respectively, and the specific chemical formula is Li 1-y Zr y Fe 1-x Ti x PO4 / C (where 0.001≦x≦0.05, 0.001≦y≦0.02), titanium is doped on the Fe site, zirconium is doped on the Li site, and the carbon content in the product is 0.5-5.0 wt%.

[0018] In the method for producing a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium according to the present invention, a mixture of iron phosphate, lithium carbonate, a carbon source, a titanium source, and a zirconium source mixed in a liquid phase solvent is ground into a slurry having a predetermined particle size using a ball mill and a sand mill, and then granulated by a spray drying means, and the dried sprayed material is sintered and pulverized in an atmospheric furnace to obtain a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium. Specifically, the method includes the following steps: (1) weighing iron phosphate, lithium carbonate, a titanium source, and a zirconium source in an elemental molar ratio of Li:Zr:Fe:Ti:P=1-y:y:1-x:x:1 (where 0.001≦x≦0.05, 0.001≦y≦0.02) and mixing them in a liquid phase solvent; (2) adding a carbon source to the mixture obtained in the step (1), and then polishing the mixture with a ball mill and a sand mill so that the particle size of the slurry is controlled to 0.1 to 0.8 μm; (3) spray-drying the slurry obtained in the step (2) under conditions of an atomization frequency of 20 to 80 Hz, an air inlet temperature of the heated air of 100 to 300°C, and an air outlet temperature of 50 to 200°C to obtain a yellow powder spray material; (4) pre-sintering the dried sprayed material obtained in the step (3) at 300 to 500°C for 2 to 5 hours in an atmosphere furnace in which a protective gas is passed, and then sintering the material at 500 to 900°C for 5 to 15 hours to produce a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium; (5) pulverizing the product after sintering to obtain a black powder product.

[0019] In the above step (1), the titanium source is one or more of titanium dioxide, titanyl sulfate, titanium tetrachloride, and tetrabutyl titanate; the zirconium source being one or more of zirconium oxide, zirconium hydroxide, zirconium nitrate, and zirconium phosphate; The liquid phase solvent is either or both of deionized water and absolute ethanol.

[0020] In the above step (2), the carbon source is one or more of glucose, sucrose, citric acid and polyethylene glycol, and the amount of the carbon source added is an amount that allows the carbon content in the final product to be controlled to 0.5 to 5.0 wt %.

[0021] In the above step (4), the protective gas is argon gas or nitrogen gas.

[0022] Preferably, in step (1), the titanium source is tetrabutyl titanate, the zirconium source is zirconium hydroxide, and the liquid phase solvent is deionized water.

[0023] Preferably, in step (2), the carbon source is glucose and polyethylene glycol, the carbon content in the final product is 1.5 wt %, and the particle size of the slurry is 0.4 μm.

[0024] Preferably, in step (3), the atomization frequency is 60 Hz, the inlet temperature of the heated air is 200°C, and the outlet temperature of the heated air is 100°C.

[0025] Preferably, in step (4), the protective gas is Ar, the preliminary sintering is carried out at a temperature of 350° C. for 3 hours, and the sintering is carried out at a temperature of 800° C. for 10 hours. EXAMPLES

[0026] The present invention will be further described below based on specific embodiments.

[0027] Example 1 Iron phosphate, lithium carbonate, tetrabutyl titanate, and zirconium hydroxide were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.985:0.015:0.99:0.01:1 and mixed in deionized water. Glucose was then added to the mixture, followed by ball mill and sand mill treatment to control the slurry particle size to 0.4 μm. The slurry was spray-dried under the conditions of an atomization frequency of 50 Hz, an air inlet temperature of the heated air of 200°C, and an air outlet temperature of 100°C. Finally, the dried spray material was pre-sintered at 350°C for 3 hours in an atmosphere furnace filled with argon gas, and then sintered at 800°C for 10 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 0.5 wt% and a discharge capacity of 158.3 mAhg at 0.1 C. -1 , initial coulombic efficiency of 98.4%, discharge capacity at 1C of 145.5mAhg -1 , compressed density is 2.52gmL -1 It was.

[0028] Example 2 Iron phosphate, lithium carbonate, titanium dioxide, and zirconium oxide were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.98:0.02:0.96:0.04:1 and mixed in deionized water. Sucrose was then added to the mixture, followed by ball mill and sand mill processing to control the slurry particle size to 0.2 μm. The slurry was spray-dried under the following conditions: atomization frequency of 60 Hz, air inlet temperature of the heated air of 150°C, and air outlet temperature of 70°C. Finally, the dried spray material was pre-sintered at 300°C for 5 hours in an atmospheric furnace filled with nitrogen gas, and then sintered at 750°C for 12 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 1.1 wt% and a discharge capacity of 159.1 mAhg at 0.1 C. -1 , initial coulombic efficiency of 97.3%, discharge capacity at 1C of 148.0mAhg -1 , compressed density is 2.38gmL -1 It was.

[0029] Example 3 Iron phosphate, lithium carbonate, titanyl sulfate, and zirconium nitrate were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.985:0.015:0.99:0.02:1 and mixed in anhydrous ethanol. Then, citric acid and polyethylene glycol were added to the mixture, and the mixture was subjected to ball mill and sand mill treatment so that the slurry particle size was controlled to 0.1 μm. The slurry was spray-dried under the conditions of an atomization frequency of 80 Hz, an air inlet temperature of the heated air of 100°C, and an air outlet temperature of 50°C. Finally, the dried spray material was pre-sintered at 380°C for 4 hours in an atmosphere furnace filled with argon gas, and then sintered at 600°C for 12 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 2.0 wt% and a discharge capacity of 156.5 mAhg at 0.1 C. -1 , initial coulombic efficiency of 95.3%, discharge capacity at 1C of 140.2mAhg -1 , compressed density is 2.25gmL -1 It was.

[0030] Example 4 Iron phosphate, lithium carbonate, titanium tetrachloride, tetrabutyl titanate, zirconium nitrate and zirconium phosphate were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.995:0.005:0.95:0.05:1 and mixed in deionized water. Glucose was then added to the mixture, followed by ball mill and sand mill treatment to control the slurry particle size to 0.5 μm. The slurry was spray-dried under the conditions of an atomization frequency of 50 Hz, an air inlet temperature of the heated air of 180°C, and an air outlet temperature of 90°C. Finally, the dried spray material was pre-sintered at 320°C for 4 hours in an atmosphere furnace filled with argon gas, and then sintered at 500°C for 12 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 3.5 wt% and a discharge capacity of 153.3 mAhg at 0.1 C. -1 , initial coulombic efficiency of 94.1%, discharge capacity at 1C of 135.3mAhg -1 , compressed density is 2.15gmL -1 It was.

[0031] Example 5 Iron phosphate, lithium carbonate, titanium tetrachloride, and zirconium phosphate were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.999:0.001:0.98:0.02:1 and mixed in deionized water. Sucrose and citric acid were then added to the mixture, followed by ball mill and sand mill treatment to control the slurry particle size to 0.6 μm. The slurry was spray-dried under the conditions of an atomization frequency of 40 Hz, an air inlet temperature of the heated air of 220°C, and an air outlet temperature of 120°C. Finally, the dried spray material was pre-sintered at 430°C for 3 hours in an atmospheric furnace filled with nitrogen gas, and then sintered at 800°C for 9 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 1.5 wt% and a discharge capacity of 159.2 mAhg at 0.1 C. -1 , initial coulombic efficiency of 96.5%, discharge capacity at 1C of 139.0mAhg -1 , compressed density is 2.39gmL -1 It was.

[0032] Example 6 Iron phosphate, lithium carbonate, titanium dioxide, titanyl sulfate, titanium tetrachloride, and zirconium hydroxide were weighed in the element molar ratio Li:Zr:Fe:Ti:P=0.98:0.02:0.999:0.001:1 and mixed in deionized water. Glucose and citric acid were then added to the mixture, followed by ball mill and sand mill treatment to control the slurry particle size to 0.8 μm. The slurry was spray-dried under the conditions of atomization frequency of 20 Hz, air inlet temperature of the heated air of 300°C, and air outlet temperature of 200°C. Finally, the dried spray material was pre-sintered at 500°C for 2 hours in an atmosphere furnace filled with argon gas, and then sintered at 900°C for 5 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 1.0 wt% and a discharge capacity of 155.5 mAhg at 0.1 C. -1 , initial coulombic efficiency of 94.4%, discharge capacity at 1C of 136.2mAhg -1 , compressed density is 2.55gmL -1 It was.

[0033] Example 7 Iron phosphate, lithium carbonate, tetrabutyl titanate, zirconium oxide, zirconium hydroxide and zirconium nitrate were weighed in an element molar ratio of Li:Zr:Fe:Ti:P=0.99:0.01:0.97:0.03:1 and mixed in anhydrous ethanol. Sucrose, citric acid and polyethylene glycol were then added to the mixture, which was then subjected to ball mill and sand mill treatment to control the slurry particle size to 0.7μm. The slurry was spray-dried under the conditions of an atomization frequency of 30Hz, an air inlet temperature of the heated air of 280℃ and an air outlet temperature of 150℃. Finally, the dried spray material was pre-sintered at 400℃ for 2 hours in an atmospheric furnace filled with nitrogen gas, and then sintered at 850℃ for 7 hours. The sintered product was pulverized to obtain a black powder titanium and zirconium co-doped carbon-coated lithium iron phosphate material. This material had a carbon content of 5.0wt% and a discharge capacity of 157.0mAhg at 0.1C. -1 , initial coulombic efficiency of 96.2%, discharge capacity at 1C of 140.5mAhg-1 , compressed density is 2.35gmL -1 It was.

[0034] In addition, in the present invention, an undoped carbon-coated lithium iron phosphate material, i.e., no titanium source and zirconium source were added during the preparation, was adopted as a comparative example. It can be seen from Figures 1, 2 and 3 that the co-doping of titanium and zirconium effectively improved the electrochemical properties of the carbon-coated lithium iron phosphate, and a cathode material for lithium ion batteries with high energy and high power density was obtained.

[0035] In the present invention, the Fe site and Li site in the carbon-coated lithium iron phosphate material are doped with titanium ions and zirconium ions, respectively, so that the electrochemical properties and compaction density of the lithium iron phosphate material can be effectively improved, and it is very suitable for use as a positive electrode material for high-energy and high-power density lithium ion power batteries. The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. It is easily understood by those skilled in the art that any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the protection scope of the present invention.

Claims

1. Chemical formula: Li 1-y Zr y Fe 1-x Ti x P.O. 4 A carbon-coated lithium iron phosphate material co-doped with titanium and zirconium, characterized in that the material is represented by the formula: x≦0.05, y≦0.02, and titanium is doped at the Fe site, and zirconium is doped at the Li site.

2. The carbon-coated lithium iron phosphate material co-doped with titanium and zirconium according to claim 1, characterized in that the carbon content of the carbon-coated lithium iron phosphate material co-doped with titanium and zirconium is 0.5-5.0 wt%.

3. 2. A method for producing a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium according to claim 1, comprising: grinding a mixture of iron phosphate, lithium carbonate, a carbon source, a titanium source, and a zirconium source in a liquid phase solvent with a ball mill and a sand mill to obtain a slurry of a predetermined particle size, spray-drying the slurry with a spray-drying means, and sintering and pulverizing the material obtained by spray-drying in an atmospheric furnace to obtain a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium.

4. (1) weighing iron phosphate, lithium carbonate, a titanium source, and a zirconium source in an elemental molar ratio of Li:Zr:Fe:Ti:P=1-y:y:1-x:x:1 (where 0.001≦x≦0.05, 0.001≦y≦0.02) and mixing them in a liquid phase solvent; (2) adding a carbon source to the mixture obtained in the step (1), and then polishing the mixture with a ball mill and a sand mill so that the particle size of the slurry is controlled to 0.1 to 0.8 μm; (3) spray-drying the slurry obtained in the step (2) under conditions of an atomization frequency of 20 to 80 Hz, an air inlet temperature of the heated air of 100 to 300° C., and an air outlet temperature of 50 to 200° C.; (4) a step of pre-sintering the dried sprayed material obtained in the step (3) at 300 to 500°C for 2 to 5 hours in an atmosphere furnace through which a protective gas is passed, and then sintering the material at 500 to 900°C for 5 to 15 hours to produce a carbon-coated lithium iron phosphate material co-doped with titanium and zirconium, according to claim 3, wherein the protective gas is argon gas or nitrogen gas.

5. 5. The method for producing titanium and zirconium co-doped carbon coated lithium iron phosphate material according to claim 4, characterized in that the titanium source is one or more of titanium dioxide, titanyl sulfate, titanium tetrachloride and tetrabutyl titanate.

6. 5. The method of claim 4, wherein the zirconium source is one or more of zirconium oxide, zirconium hydroxide, zirconium nitrate, and zirconium phosphate.

7. 5. The method of claim 4, wherein the liquid phase solvent is either or both of deionized water and absolute ethanol.

8. the carbon source is one or more of glucose, sucrose, citric acid, and polyethylene glycol; The method for producing the titanium and zirconium co-doped carbon-coated lithium iron phosphate material according to claim 4, characterized in that the amount of carbon source added is an amount that allows the carbon content in the final product to be 0.5-5.0 wt%.

9. The atomization frequency is 60 Hz, the air inlet temperature is 200° C., and the air outlet temperature is 100° C.; The temperature of the preliminary sintering is 400° C., and the time of the preliminary sintering is 3 hours. The method for preparing titanium and zirconium co-doped carbon-coated lithium iron phosphate material according to claim 4, characterized in that the sintering temperature is 800°C, and the sintering time is 10 hours.

10. An application of a titanium and zirconium co-doped carbon-coated lithium iron phosphate material, wherein the titanium and zirconium co-doped carbon-coated lithium iron phosphate material is used as a positive electrode material in a lithium ion battery, and is characterized in that it is the titanium and zirconium co-doped carbon-coated lithium iron phosphate material as described in claim 1 or 2.

Citation Information

Patent Citations

  • Method for preparing high-density lithium ferric phosphate

    CN102009970A

  • Method for preparing spherical LFP (lithium iron phosphate) / carbon doped composite powder

    CN102044667A

  • A high magnification spherical lithium iron phosphate carbon composite positive electrode material and a preparation method thereof

    CN109192953A

  • Modified lithium iron phosphate material and preparation method thereof

    CN112978704A

  • Conductive lithium storage electrode

    JP2005514304A